2001
DOI: 10.1002/jcb.1277
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of G3BPs: Tissue specific expression, chromosomal localisation and rasGAP120 binding studies

Abstract: The G3BP (ras-GTPase-Activating Protein SH3-Domain-Binding Protein) family of proteins has been implicated in both signal transduction and RNA-metabolism. We have previously identified human G3BP-1, G3BP-2, and mouse G3BP-2. Here, we report the cloning of mouse G3BP-1, the discovery of two alternatively spliced isoforms of mouse, and human G3BP-2 (G3BP-2a and G3BP-2b), and the chromosomal localisation of human G3BP-1 and G3BP-2, which map to 5q14.2-5q33.3 and 4q12-4q24 respectively. We mapped the rasGAP(120) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
99
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(101 citation statements)
references
References 35 publications
2
99
0
Order By: Relevance
“…The G3BP family includes two members in mammals, G3BP1 (referred to as G3BP) and G3BP2 8 . Both proteins colocalize in SGs, when cells are subjected to stress 9 .…”
Section: Introductionmentioning
confidence: 99%
“…The G3BP family includes two members in mammals, G3BP1 (referred to as G3BP) and G3BP2 8 . Both proteins colocalize in SGs, when cells are subjected to stress 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Ras-GTPase-activating protein-SH3-domain-binding proteins 1 and 2 (G3BP1 and 2) are close structural homologues that share 59% identity at the primary sequence level (Kennedy et al, 2001). These proteins directly associate with the SH3 domain of GTPaseactivating protein (GAP), which functions as an inhibitor of Ras (Tocque et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…G3BP2b is a splice isoform of G3BP2a, lacking 33 amino acids in the central region (Kennedy et al, 2001). Figure 1 is a linear representation of the three G3BPs showing the arrangement of known domains possessed by these proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Although G3BP1 was initially isolated as a RasGAP SH3 domain binding protein and all three G3BPs have subsequently been shown to bind the SH3 domain of RasGAP (Kennedy et al, 2001, Parker et al, 1996, PxxP motifs have not been shown to mediate this interaction. In vitro binding assays with G3BP1 and G3BP2 suggested that the NTF2-like domain of these proteins was responsible for RasGAP binding (Kennedy et al, 2001). It is rare, but not unprecedented, for non-proline motifs to bind SH3 domains (Agrawal and Kishan, 2002).…”
Section: Introductionmentioning
confidence: 99%